Utilization of Microsoft Mathematics Applications as Learning Tool in Improving Student Learning Outcomes - Awaludin Fitra; Yulia Utami; Martua Sitorus (International Journal of Education, Information Technology, and Others, 2020)
This research is quasi-experimental. Which aims to determine the differences in student learning outcomes taught by learning by using Microsoft Mathematics and Conventional Learning applications on the subject of Two Variable Linear Equation Systems in class VIII SMP Kemala Bhayangkari 1 Medan. The sample in this study was carried out by random sampling from 2 existing classes, namely class VIIIA and VIIIB. In the homogeneity test, the test data obtained was Fcount = 1.605. After comparing the price of Fcount with Ftable, with n = 54 and the real level α = 0.05, the price of Ftable = 2.48 is obtained. It turns out that Fcount <Ftable (1.605 < 2.48), then the student learning outcomes for both classes have the same variance in other words the two classes are homogeneous. In testing the hypothesis, it is obtained tcount = 4.064 and the value of ttable at dk = 52 and the real level α = 0.05 is t table = 1.675. Then tcount> ttable (4.064 > 1.675). So that the average student learning outcomes in the experimental class are higher than the control class and from the results of hypothesis testing are significantly fulfilled, it can be concluded that the learning outcomes of students using Microsoft Mathematics assisted learning are higher than conventional learning.